Behavioral and performance jellyfish attack - Layth A. Khalil Al Dulaimi; R. Badlishah Ahmad; Naimah Yaakob; Syadiah Nor Wan Shamsuddin; Mohamed Elshaikh (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Wwe provide a simulation-based study of the effects of jellyfish attacks on mobile ad hoc networks (MANETs). For this purpose we suggest a simulation based on the effects of jellyfish attacks on the network through a number of different scenarios. In particular, we examine how the number of attackers affects performance measures such as the ratio of packet delivery, throughput, and end-to-end delays. The results have enabled us to propose measures to reduce the effects of jellyfish attacks on MANETs.